2013
DOI: 10.1136/gutjnl-2013-304562
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic versus histological characterisation of polyps during screening colonoscopy

Abstract: NCT01297712.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
52
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(60 citation statements)
references
References 35 publications
4
52
1
3
Order By: Relevance
“…3 Various studies have shown that using modern endoscopic technology, such as narrow-band imaging, endoscopists can predict neoplastic polyps with high accuracy and apply the resect and discard strategy for diminutive polyps. [13][14][15] However, a recent study evaluating the ability of community endoscopists to diagnose in vivo polyp type showed an accuracy of only 76.6%, 16 lower than ASGE-PIVI standards.…”
Section: Discussionmentioning
confidence: 96%
“…3 Various studies have shown that using modern endoscopic technology, such as narrow-band imaging, endoscopists can predict neoplastic polyps with high accuracy and apply the resect and discard strategy for diminutive polyps. [13][14][15] However, a recent study evaluating the ability of community endoscopists to diagnose in vivo polyp type showed an accuracy of only 76.6%, 16 lower than ASGE-PIVI standards.…”
Section: Discussionmentioning
confidence: 96%
“…All colonic hyperplastic polyps were selected from a previously published study [18] on the endoscopic differential diagnosis of colonic polyps, which had been originally interpreted as hyperplastic polyps by private practice pathologists. Out of these, hyperplastic polyps that were distally located (below the splenic flexure) and were ≤5 mm in size were excluded: This was done because such small whitish polyps can usually be recognized at endoscopy as hyperplastic and are almost always histologically confirmed as such if resected or removed under biopsy.…”
Section: Case Selection and Reassessmentmentioning
confidence: 99%
“…Moreover, under conventional white light observation with 0.1% indigo carmine application, the sensitivity, specificity, and correct diagnosis rates in the diagnosis of cT1b cancer requiring surgical resection are 66.0, 95.8, and 86.3%, respectively [15]. However, there is pressure on endoscopy physicians in general clinical hospitals to perform accurate depth of invasion diagnoses when performing endoscopic diagnoses as part of screening colon endoscopies in busy clinical settings [16].…”
Section: Introductionmentioning
confidence: 99%